2000
DOI: 10.1007/s001340000777
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an electronic information system on physician workflow and data collection in the intensive care unit

Abstract: Electronic and handwritten documentation consumed equal amounts of time. Structured entry, compared to handwriting, may encourage recording of specific or otherwise unincorporated data elements resulting in a more detailed record. This suggests that user interfaces and decision support components may influence both the types and complexity of clinical data recorded by caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 16 publications
1
53
0
Order By: Relevance
“…Because of the lack of similar studies within the setting of an emergency department, we have to compare these results with those of studies performed in other settings: Apkon & Singhaviranon [17], in their study on the impact of an electronic information system on physician workflow and data collection in the intensive care unit, and Menke et al [18], in their study on a computerized clinical documentation system in a pediatric intensive care unit, found no difference regarding the amount of time consumed dependent on the charting method. Additionally, Apkon & Singhaviranon [17] report of a significantly more detailed electronic than handwritten Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the lack of similar studies within the setting of an emergency department, we have to compare these results with those of studies performed in other settings: Apkon & Singhaviranon [17], in their study on the impact of an electronic information system on physician workflow and data collection in the intensive care unit, and Menke et al [18], in their study on a computerized clinical documentation system in a pediatric intensive care unit, found no difference regarding the amount of time consumed dependent on the charting method. Additionally, Apkon & Singhaviranon [17] report of a significantly more detailed electronic than handwritten Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…In an ICU various systems are used for collecting different data [6]. These systems include medical devices, laboratory systems, patients demographics, EMR (Electronic Medical Record), pharmacy system and end users.…”
Section: Apps For Work Flow Automationmentioning
confidence: 99%
“…Some studies point to potential EHR-related quality and safety gains due to increased adherence to guideline-based care, 1,2 more complete documentation, 3,4 and fewer medical errors. 5,6 Efficiency gains have been shown to result from electronic ordering 7,8 and from improved access to clinical information, 9,10 which can reduce redundant services.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in large health systems and hospital settings have documented both increased work hours for clinicians as well as more efficient delivery of clinical care, along with the unintended creation of new work and potential safety problems following EHR implementation. 1,3,[11][12][13][14][15][16][17][18][19] A systematic review of EHR impact on efficiency concluded that "the goal of decreased documentation time is not likely to be fulfilled, especially for physicians. "…”
Section: Introductionmentioning
confidence: 99%